Intercropping Garlic (Allium Sativum) With Chilli (Capsicum Annuum L.) in the Haor Area of Kishoreganj - Khatun, MF; Islam, MS; Ali, MA; Ali, MO; Ahmed, QM (Bangladesh Agronomy Journal, 2020)
Haor is one of the uncertain areas for crop production and productivity in Bangladesh. Traditionally, single cropping practice in a short cropping season is the key obstacle to increase crop productivity. A study was carried out at Multi Location Testing site (MLT), Nikly under the On-Farm Research Division (OFRD), Bangladesh Agricultural Research Institute (BARI), Kishoreganj at haor area during the two consecutive Rabi seasons of 2015-16 and 2016-17 to evaluate the performance of garlic with chilli intercropping system, its productivity and economic viability. Four treatments were consisted viz., sole chilli, one row garlic in between chilli rows, double rows garlic in between chilli rows and garlic with broadcasting chilli. The highest chilli equivalent yield (28 t ha-1) was obtained from one row garlic in between chilli rows and the minimum chilli equivalent yield was (15 t ha-1) obtained in sole chilli. These intercropping practices yield increased 25-89% over the sole chilli. The highest gross return (Tk.559400 ha-1), gross margin (Tk. 428240 ha-1) and BCR (4.26) were found in one row garlic in between chilli rows and the lowest gross return (Tk. 297800 ha-1) and gross margin (Tk.188080 ha-1) were obtained from sole chilli but the lowest BCR (1.74) in double rows garlic in between chilli rows. Considering the experimental findings of two years, one row garlic in between chilli rows would be a suitable intercropping system for higher productivity and economic return. Bangladesh Agron. J. 2020, 23(1): 75-81